2009
DOI: 10.1016/j.vetmic.2009.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterization of porcine group C rotaviruses in South Korea

Abstract: Group C rotaviruses (GCRVs) cause acute diarrhea in humans and animals worldwide and the evidence for a possible zoonotic role of GCRVs has been recently provided. However, there is little evidence of porcine GCRV infections or of their genetic diversity in South Korea. We examined 137 diarrheic fecal specimens from 55 farms collected from six provinces. RT-PCR utilizing primer pairs specific for the GCRV VP6 gene detected GCRV-positive reactions in 36 (26.2%) diarrheic fecal samples. Of these, 17 samples (12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
46
5
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 53 publications
11
46
5
1
Order By: Relevance
“…The authors previously reported that the prevalence of porcine GCRV infections in South Korea is 26% of the surveyed diarrheic fecal samples by conventional RT-PCR. 10 However, the present findings by both real-time RT-PCR assays indicate that the fecal prevalence of the porcine GCRVs in piglet diarrhea is much higher than that reported previously in South Korea. 10 Although RT-PCR has been used for the detection of porcine GCRV, 4,10 this assay cannot measure the viral load in the stool samples, resulting in a significant gap in veterinary knowledge about virological and epidemiological features.…”
contrasting
confidence: 80%
See 3 more Smart Citations
“…The authors previously reported that the prevalence of porcine GCRV infections in South Korea is 26% of the surveyed diarrheic fecal samples by conventional RT-PCR. 10 However, the present findings by both real-time RT-PCR assays indicate that the fecal prevalence of the porcine GCRVs in piglet diarrhea is much higher than that reported previously in South Korea. 10 Although RT-PCR has been used for the detection of porcine GCRV, 4,10 this assay cannot measure the viral load in the stool samples, resulting in a significant gap in veterinary knowledge about virological and epidemiological features.…”
contrasting
confidence: 80%
“…10 However, the present findings by both real-time RT-PCR assays indicate that the fecal prevalence of the porcine GCRVs in piglet diarrhea is much higher than that reported previously in South Korea. 10 Although RT-PCR has been used for the detection of porcine GCRV, 4,10 this assay cannot measure the viral load in the stool samples, resulting in a significant gap in veterinary knowledge about virological and epidemiological features. Therefore, the copy number of porcine GCRV in the stool samples by real-time RT-PCR assays was evaluated.…”
contrasting
confidence: 80%
See 2 more Smart Citations
“…Relevance of RVC is being augmented because piggery constitutes the main livelihood framework of rural and tribal population in many developing countries along with the possibility of zoonotic potential as indicated in earlier studies (Iturriza-Gomara et al 2004;Gabbay et al 2008). Detection of porcine-type RV in bovine sample and bovine-type isolate in porcine sample (Jeong et al 2009) also support the possibility of species jumping or re-assortment events. In India, only human RVCs are identified till to date (Brown et al 1988) and this group of RV could not mark its presence in other species before.…”
Section: Introductionmentioning
confidence: 74%